2018
DOI: 10.1523/eneuro.0183-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Interlimb Generalization of Learned Bayesian Visuomotor Prior Occurs in Extrinsic Coordinates

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 77 publications
4
21
0
Order By: Relevance
“…The two different task contexts we investigated in this work are distinct to previous studies, as we did not test generalization from one effector to another, such as performing a task with the right hand and switching to the left (Hewitson et al, 2018;Kumar et al, 2020), or switching from a motor to a perceptual task (Chambers et al, 2019). Instead, our two contexts represent two distinct cue-action mappings, though performed with the same motor system (oculomotor).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two different task contexts we investigated in this work are distinct to previous studies, as we did not test generalization from one effector to another, such as performing a task with the right hand and switching to the left (Hewitson et al, 2018;Kumar et al, 2020), or switching from a motor to a perceptual task (Chambers et al, 2019). Instead, our two contexts represent two distinct cue-action mappings, though performed with the same motor system (oculomotor).…”
Section: Discussionmentioning
confidence: 99%
“…However, previous findings regarding the generalization of statistical priors have been mixed. Some studies have shown that statistical learning of priors is very narrow-band and context/modality-specific in perceptual (Frost et al, 2015) and sensorimotor domains (Hewitson et al, 2018;Yin et al, 2019), thus preventing learned information to transfer to different contexts/modalities. Other studies, on the other hand, provided evidence for generalization (Sato and Kording, 2014;Kiryakova et al, 2020), although generalization, in some instances, seemed to occur differently for different parameters of a statistical distribution; e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The two different task contexts we investigated in this work are distinct to previous studies, as we did not test generalization from one effector to another, such as performing a task with the right hand and switching to the left [11,21], or switching from a motor to a perceptual task [16]. Instead, our two contexts represent two distinct cue-action mappings, though performed with the same modality (oculomotor system).…”
Section: Discussionmentioning
confidence: 99%
“…However, previous findings regarding the generalization of statistical priors have been mixed. Some studies have shown that statistical learning of priors is very narrow-band and context/modality-specific in perceptual [10] and sensorimotor domains [11,12], thus preventing learned information to transfer to different contexts/modalities. Other studies, on the other hand, provided evidence for generalization [4,13], although generalization, in some instances, seemed to occur differently for different parameters of a statistical distribution; e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These can be varied relative to each other by keeping the body position the same while varying visual stimuli, or by doing the reverse. Some results suggest that, for certain tasks, generalization can occur entirely within a representation of extrinsic space, for instance by showing that learned forward models generalize across limbs (Hewitson, Sowman, & Kaplan, 2018). For other kinds of tasks, generalization is strongest only when novel tasks are similar in both intrinsic and extrinsic space (Carroll, Poh, & de Rugy, 2014).…”
Section: Generalizationmentioning
confidence: 99%